2018
DOI: 10.3390/ijms19082356
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Analysis of the Outer Membrane Vesicles from Paired Polymyxin-Susceptible and -Resistant Klebsiella pneumoniae Clinical Isolates

Abstract: Gram-negative bacteria produce outer membrane vesicles (OMVs) as delivery vehicles for nefarious bacterial cargo such as virulence factors, which are antibiotic resistance determinants. This study aimed to investigate the impact of polymyxin B treatment on the OMV lipidome from paired polymyxin-susceptible and -resistant Klebsiella pneumoniae isolates. K. pneumoniae ATCC 700721 was employed as a reference strain in addition to two clinical strains, K. pneumoniae FADDI-KP069 and K. pneumoniae BM3. Polymyxin B t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
(60 reference statements)
4
18
0
Order By: Relevance
“…The authors hypothesized that these cells may use OMV formation as a way to selectively remove environmentally disadvantageous LPS species from the outer membrane under certain conditions. Another study showed that the size and lipid composition of Klebsiella pneumoniae OMVs was altered after polymyxin treatment, suggesting that the lipid composition of OMVs reflects the outer membrane remodeling associated with cell envelope stress induced by polymyxin (Jasim et al, 2018). In contrast, several studies have suggested a mechanism in which certain proteins determine the MV composition.…”
Section: What Determines MV Composition?mentioning
confidence: 99%
“…The authors hypothesized that these cells may use OMV formation as a way to selectively remove environmentally disadvantageous LPS species from the outer membrane under certain conditions. Another study showed that the size and lipid composition of Klebsiella pneumoniae OMVs was altered after polymyxin treatment, suggesting that the lipid composition of OMVs reflects the outer membrane remodeling associated with cell envelope stress induced by polymyxin (Jasim et al, 2018). In contrast, several studies have suggested a mechanism in which certain proteins determine the MV composition.…”
Section: What Determines MV Composition?mentioning
confidence: 99%
“…The core lipids of K. intermedius, which serve as the framework for fully mature membrane lipids, are PLs, triglycerides, FAs, and sterols. Typical membrane parameters adversely affected by environmental challenges are permeability and fluidity, which, in turn, affect the function and mobility of membrane proteins, diffusion of nutrients, and energy sources (Rowlett et al, 2017;Siliakus et al, 2017;Jasim et al, 2018). In our study, the most striking changes were recorded in the membranes of OMVs from the UV-exposed K. intermedius, compared to the OMVs from K. intermedius/iKMC, and this correlated with increased synthesis of lipids, especially, PLs, free FAs, and sterols, which could cause alteration in membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria form vesicles in broth culture, on solid media, in biofilms, and during intracellular and extracellular survival as part of pathogenic and mutualistic relationships with eukaryotes (166)(167)(168). Certain conditions favor blebbing, such as elevated temperature, interactions with quorum-sensing quinolones, antibiotic exposure, encounters with bacteriophage endolysins, and nutrient deprivation (169)(170)(171)(172)(173)(174). Their existence was described half of a century ago, yet we still do not firmly grasp how Gram-negative bacteria control OMV formation and regulate the secretion of lipids into their environment.…”
Section: Outer Membrane Vesicle Biogenesismentioning
confidence: 99%